Age-independent first trimester screening for Down syndrome: analysis of three modified software programs with 6,508 pregnancies - Hörmansdörfer, Cindy; Golatta, Michael; Scharf, Alexander; Hillemanns, P.; Schmidt, P. (Archives of gynecology and obstetrics, 2011)
Background: The conventional first trimester screening (FTS) method integrates maternal age into risk calculation. It was suggested that this concept increases the false-positive rate in older, and the false-negative rate in younger mothers. Materials and methods: Six thousand five hundred and eight combined FTS with known fetal outcome underwent regular risk calculation with the software programs Pia fetal database (PIA) (GE-ViewPoint, GE Medical Systems), prenatal risk calculation (PRC) (Version 1.0.61, gmt/nexus), and JOY (Version 2.1, PET software). The results were mathematically modified as if generated with age-independent software (PIAmod, PRCmod, and JOYmod). Results: 17 of 40 trisomy 21 cases were present in women younger than 35. A right shift in the mean maternal age of false-negative cases occurred in all programs (PIA: 30.00, PIAmod: 32.00, PRC: 30.00, PRCmod: 32.25, JOY: 30.00, JOYmod: 34.50). The overall false-positive rate declined by −40.03% (PIAmod), −38.64% (PRCmod), and −37.50% (JOYmod) and in women over 35 (40) years by −72.37, −73.45, and −73.20% (−89.04, −90.33, and −90.56%), being then as high as in the other age groups. Conclusion: First trimester screening would become reasonable in women over 40 years. However, women over 35 would also be more often affected by false-negative results. The implications of a concept adaptation should be analyzed in a large prospective study.
Published online: 3 April 2010
Gesehen am 29.06.2022